2020
DOI: 10.1515/cclm-2020-0306
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/phenotype relationship in Gaucher disease patients. Novel mutation in glucocerebrosidase gene

Abstract: AbstractObjectivesGaucher disease (GD) is the most common inherited lysosomal storage disease, caused by mutations in acid β-glucosidase (GBA) gene. This study aimed to identify mutations in Andalusia patients with GD and their genotype-phenotype correlation.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…GBA analysis revealed that she was homozygous for the p.L483P (c.1448 T > C) variant. p.L483P is the most common pathogenic variant in Japanese patients with GD [ 22 ] and is involved in the development of neurological symptoms [ 23 , 24 ]. ERT was started at the age of 84 days and improved her anemia, thrombocytopenia, and hepatosplenomegaly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GBA analysis revealed that she was homozygous for the p.L483P (c.1448 T > C) variant. p.L483P is the most common pathogenic variant in Japanese patients with GD [ 22 ] and is involved in the development of neurological symptoms [ 23 , 24 ]. ERT was started at the age of 84 days and improved her anemia, thrombocytopenia, and hepatosplenomegaly.…”
Section: Resultsmentioning
confidence: 99%
“…This variant is the most frequent in patients with neuropathic GD [ 33 ] and Japanese patients with GD [ 22 ]. Although most patients with the homozygous p.L483P variant develop GD3 [ 24 , 30 ], they may have a variety of clinical courses [ 23 ]. There is an unclear relationship between the clinical course of GD and residual GCase activity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing can be done as a primary test for GD diagnosis. However, since many GBA1 variants are private, the chances of finding variants of uncertain significance (VUS) are quite high [25,[143][144][145][146][147][148][149][150][151][152][153][154][155]. In this case, confirmation of diagnosis through the assessment of enzymatic activity in patient's cells is mandatory.…”
Section: What Is the Role Of Genetic Testing In The Diagnosis Of Gd?mentioning
confidence: 99%
“…While 4 pathogenetic variants (N370S; L444P, c.84-85 insG; IVS + 1G > A) account for 90% of alleles within Ashkenazi Jews, they account only for about 50-75% of alleles in non-Jewish populations. In addition, about 10% of patients present large deletions/ recombinant alleles [25,[143][144][145][146][147][148][149][150][151][152][153][154][155][157][158][159][160][161][162][163][164].…”
Section: What Is the Role Of Genetic Testing In The Diagnosis Of Gd?mentioning
confidence: 99%
See 1 more Smart Citation